Complexation of Syndiotactic Polystyrene with Branched Molecules. Issue 1 (14th August 2019) - Kaneko, Fumitoshi; Radulescu, Aurel; Iwase, Hiroki; Takata, Shin‐ichi; Nishiura, Masayoshi; Hou, Zaomin
Abstract : Syndiotactic polystyrene (sPS) forms cocrystals with a wide range of chemical species from low‐mass molecules to polymeric compounds, such as polyethylene glycols. Although the sPS lattice has been confirmed to accept linear compounds, such as n‐alkanes and n‐fatty acids, branched molecules have not been regarded as guests until now. To investigate whether sPS can adopt branched molecules as guests, cocrystallization using three types of monoacid triacylglycerols (TAGs) with relatively short acyl chains, tricaprin, trilaurin, and trimyristin has been attempted. Moreover, the sPS films subjected to the guest exchange procedure have been investigated via X‐ray diffraction, Fourier transform infrared spectroscopy, and simultaneous small‐ and wide‐angle neutron scattering. The results showed that sPS forms the monoclinic δ clathrate cocrystal with all the three TAGs.